Cultural issues in the treatment of hospitalised, malnourished children : an exploratory-descriptive study of the attitudes of health professionals and mothers in a rural hospital setting - Motswaledi, Mmabotsha (Department of Social Development, 2016)
Bibliography: p. 100-105.